A novel and efficient route for the syntheses of hydroxylated 2,3-diarylxanthones - Santos, Clementina M.M. (2011)
A novel, efficient and general route for the synthesis of hy-droxylated 2,3-diarylxanthones is described. 3-Bromo-2-styrylchromones, the key intermediate of this synthesis, is obtained by a Baker-Venkataraman rearrangement of appropriate 2’-cinnamoyloxyacetophenones, followed by a one-pot reaction with phenyltrimethylammonium tribromide. The Heck reaction of these bromochromones with substituted styrenes gives methoxylated 2,3-diarylxanthones. The cleavage of the methyl groups with BBr3 gives the desired hydroxylated 2,3-diarylxanthones.